Participatory evaluation : tools for managing change in water and sanitation - Narayan-Parker, Deepa (Washington, D.C. : World Bank, 1993)
This documents provides policymakers, managers and planning and evaluation staff with ideas about participatory process and indicators that can be used to involve community members and others in program evaluation.
Includes bibliographical references (p. 120-121).
osa 22/01/19
Loans
Keywords: Water-supply, Rural; Sanitation, Rural